FUNCTIONAL ORGANIZATIONS CONCEPT OF THE POLYTECHNIC UNIVERSITY TYPICAL INFORMATION RESOURCES INTERNET PORTAL - Babenko, B.O.; Babina, T.B.; Gabzovska, О.Б.; Savitsky, А.Й. (Journal of Information Technologies in Education (ITE), 2010)
Functional organizations concept of the polytechnic university typical information resources Internet portal are presented by subsystems, services, WEB-resources and information areas. Typical functional architecture of the university information resources Internet portal is showed.